2020
DOI: 10.1530/rep-20-0277
|View full text |Cite
|
Sign up to set email alerts
|

Equine pregnancy-specific glycoprotein CEACAM49 secreted by endometrial cup cells activates TGFB

Abstract: In early equine pregnancy a highly invasive trophoblast cell subpopulation, the chorionic girdle cells, invade the endometrium and form endometrial cups (EC). These cells express classical MHC molecules, thereby stimulating a humoral and cellular immune response, resulting in a massive accumulation of maternal CD4+ and CD8+ T cells around the EC. Nevertheless, no immediate destruction of endometrial cups by maternal lymphoid cells occurs, presumably due to immune tolerance. Although the environment of EC is ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Therefore, we assumed that the AP-1 transcription factor complex may also play important roles in equine CG differentiation and invasion. Additionally, the transforming growth factor-beta (TGFB) family plays a role in controlling the trophoblast cells invasion ( Lash et al, 2005 ), and the TGFB is activated in equine endometrial cups cells to maintain immune tolerance ( Kammerer et al, 2020 ). In our result, we also found that the TGFB1 expression is significantly higher in binuclear CG cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assumed that the AP-1 transcription factor complex may also play important roles in equine CG differentiation and invasion. Additionally, the transforming growth factor-beta (TGFB) family plays a role in controlling the trophoblast cells invasion ( Lash et al, 2005 ), and the TGFB is activated in equine endometrial cups cells to maintain immune tolerance ( Kammerer et al, 2020 ). In our result, we also found that the TGFB1 expression is significantly higher in binuclear CG cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction (2022) 163 R11-R23 classification of the equine proteins as PSGs because the inhibition of platelet -fibrinogen interactions (Aleksic et al 2016) -and activation of TGF-β (Kammerer et al 2020), which are conserved functions of human and mouse PSGs, are not exhibited by non-placentaexpressed CEACAMs in any species.…”
Section: R13mentioning
confidence: 99%
“…Notwithstanding the rapid evolution of the PSG loci, the encoded proteins share many identical functions in all species examined, including in human, mouse and horse (Moore & Dveksler 2014, Aleksic et al 2016, Kammerer et al 2020. Therefore, the expansion and rapid evolution of PSG families are currently better explained by selection for increased gene product dosage than for diversification of functions.…”
Section: Psgs Are Encoded By Rapidly Evolving Multigene Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that regulatory T-cells play a role in tolerance of the invasive trophoblast ( 145 ). Since at least one of the equine PSGs can activate TGFβ1, they may contribute to differentiation of regulatory T-cells ( 146 ) as shown for human and mouse ( 130 ). PSG expression has not been examined beyond 36 days ( 142 ) and it would be interesting to know if the putative protection is withdrawn at a later stage when the cups become necrotic and eventually are sloughed off.…”
Section: Immunosuppressionmentioning
confidence: 99%